2020
DOI: 10.1080/15592324.2020.1766851
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that AGL17 is a significant downstream target of CLF in floral transition control

Abstract: Polycomb-group (PcG) proteins are evolutionarily conserved in higher organisms and play essential roles in many developmental processes by catalyzing the trimethylation of histone H3 lysine 27 (H3K27me3), a key repressive histone mark. In Arabidopsis (Arabidopsis thaliana), histone methyltransferase CURLY LEAF (CLF) is one of the major PcG catalytic components, playing critical roles in plant growth and development, especially the floral transition. We have recently profiled the genome-wide occupancy of CLF by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…AGL61 , a homolog of IbMADS83 , functions as a TF that controls the expression of downstream genes during central cell development and is involved in the seed endosperm development ( Steffen et al, 2008 ). And AGL17 , the homolog of IbMADS31 , is a significant downstream target of CURLY LEAF in floral transition control ( Shu et al, 2020 ). We found that cis -acting elements like the MeJA-responsive elements, auxin-responsive elements, abscisic acid-responsive elements, and gibberellin-responsive elements in the promoter region of IbMADS31 and IbMADS83 provided indirect evidences for the involvement of IbMADS31 and IbMADS83 in the flower and fruit development of sweet potato.…”
Section: Discussionmentioning
confidence: 99%
“…AGL61 , a homolog of IbMADS83 , functions as a TF that controls the expression of downstream genes during central cell development and is involved in the seed endosperm development ( Steffen et al, 2008 ). And AGL17 , the homolog of IbMADS31 , is a significant downstream target of CURLY LEAF in floral transition control ( Shu et al, 2020 ). We found that cis -acting elements like the MeJA-responsive elements, auxin-responsive elements, abscisic acid-responsive elements, and gibberellin-responsive elements in the promoter region of IbMADS31 and IbMADS83 provided indirect evidences for the involvement of IbMADS31 and IbMADS83 in the flower and fruit development of sweet potato.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the gene function of their homologies in Arabidopsis , we speculated that AGL12 and AGL17 genes may be related to the degradation of root and photoperiod regulation of flower transition in Balanophora and S. himalayana ( Han et al, 2008 ; Tapia-López et al, 2008 ; Puig et al, 2013 ; Shu et al, 2020 ), they also convergently lost AGL15 and AGL6 genes, among which AGL15 genes play roles in regulating flowering through photoperiod and somatic embryo development ( Perry et al, 1999 ) and AGL6 genes are involved in floral meristem regulation, development of floral organs, and ovule and seed, and AGL6 genes also have possible roles in the development of male and female germline and gametophyte ( Dreni and Zhang, 2016 ). Two Balanophora also lost AGL63 and TRANSPARENT TESTA16 ( TT16 ) genes in GGM13 subfamily, which are involved in fruit development, seed formation, and embryo development ( Erdmann et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…MIKC C -type genes are also involved in the regulation of floral transition. Previous studies found that SUPPRESSOR OF OVEREXPRESSION OF CONSTANS 1 ( SOC1 ) regulates flowering time and flower initiation ( Barrero-Gil et al., 2021 ); FLOWERING LOCUS C (FLC) targets SQUAMOSA PROMOTER BINDING PROTEIN-LIKE 15 ( SPL15 ) and SHORT VEGETATIVE PHASE 1 ( SVP1 ) to produce different flowering phenotypes and regulate floral transition mechanisms ( Madrid et al., 2020 ); AGL17 is a key regulator of floral transition ( Shu et al., 2020 ). MIKC C -type transcription factors play crucial roles in regulating gene expression under various abiotic stress conditions ( Saha et al., 2015 ; Guo et al., 2016 ; Wang et al., 2018 ; Chen et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%